Can factitious disorder reach delusional level? A case study - Dubiel, Rafał; Perzyński, Adam; Kłębukowska, Ida; Perzyńska-Starkiewicz, Aneta; Chmiel-Perzyńska, Iwona; Olajossy, Marcin (Current Problems of Psychiatry, 2017)
The paper describes a patient, who has been consulted and hospitalized multiple times, due to dermatological lesions on his face. We will present his medical history and describe circumstances leading to the final diagnosis of factitious disorder. In the theoretical part we will try to answer the question , whether the extreme severity of the factitious disorders can, at some point , reach the level of delusions.